Representation of Damar Kurung by Masmundari in Cyanotype - Catur Himawan Repatio Putro; Risman Marah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Representation of Damar Kurung Masmundari in Cynotype is a two-dimensional work of art based on the work process of creating art in a studio using the medium of photography, cyanotype printing techniques and also painting. The components in this work include research on Damar Kurung Masmundari and the archives of his work in Gresik, East Java. The background that underlies Representation of Damar Kurung Masmundari in Cynotype is as a form of my appreciation and dedication to the city of Gresik, especially the Masmundari family who have dedicated their lives to introducing and preserving Damar Kurung until now. In addition, there is a need for innovation in developing Damar Kurung so that the community can also contribute to the preservation of Damar Kurung. The process of creating this work of art provides awareness of the importance of the work of a photographer or photo artist in viewing the object from various sides of the discipline, collaborating with various other fields of art so as to create works that have value and messages that can be conveyed to the wider community. In this artwork thesis, I will also explain the work steps that I made to create this artwork as a shared learning material.